ANALISIS EFISIENSI BANK PERKREDITAN RAKYAT DI KOTA SEMARANG DENGAN PENDEKATAN DATA ENVOLEPMENT ANALYSIS - Septianto, Hendi; Widiharih, Tatik (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2010)
The research was conducted to measure rural banks (Bank Perkreditan Rakyat / BPR) efficiency level in Semarang city. The measurement was done using non parametric approach with Data Envolepment Analysis (DEA) method constant return to scale assumption (CCR model). The research was using all rural banks in SemarangÂ (16 rural banks). The result indicated that 6 rural banks were efficient and 10 rurals banks were inefficient. Â Keywords: CCR Model, Efficient, Rural Bank